2011
DOI: 10.1093/nar/gkr837
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of SRSF1 is modulated by replicational stress

Abstract: DNA ligase I-deficient 46BR.1G1 cells show a delay in the maturation of replicative intermediates resulting in the accumulation of single- and double-stranded DNA breaks. As a consequence the ataxia telangiectasia mutated protein kinase (ATM) is constitutively phosphorylated at a basal level. Here, we use 46BR.1G1 cells as a model system to study the cell response to chronic replication-dependent DNA damage. Starting from a proteomic approach, we demonstrate that the phosphorylation level of factors controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Notably, both the level of SRSF1 phosphorylation and splicing programs can revert to those observed in normal cells by inhibiting ATM activity, indicating that SRSF1 phosphorylation could be part of a regulatory circuit through which cells cope with DNA damage. In agreement with this interpretation, SRSF1 phosphorylation is modulated in response to a wide set of DNA-damaging insults (Leva et al, 2012) and SRSF1 is involved in the choice between pro- and anti-apoptotic pathways (Moore et al, 2010). …”
Section: Rbps May Affect the Splicing Profiles And Levels Of Mrnas Fosupporting
confidence: 52%
See 1 more Smart Citation
“…Notably, both the level of SRSF1 phosphorylation and splicing programs can revert to those observed in normal cells by inhibiting ATM activity, indicating that SRSF1 phosphorylation could be part of a regulatory circuit through which cells cope with DNA damage. In agreement with this interpretation, SRSF1 phosphorylation is modulated in response to a wide set of DNA-damaging insults (Leva et al, 2012) and SRSF1 is involved in the choice between pro- and anti-apoptotic pathways (Moore et al, 2010). …”
Section: Rbps May Affect the Splicing Profiles And Levels Of Mrnas Fosupporting
confidence: 52%
“…The LigI defect hampers the maturation of Okazaki fragments and results in the accumulation of single-stranded DNA breaks (SSBs) and DSBs and in the constitutive activation of the ATM checkpoint pathway (Soza et al, 2009). By applying a proteomic approach, we have shown that the entire set of SR splicing factors, particularly SRSF1, is hyper-phosphorylated in LigI-deficient cells and this modification is accompanied by a shift in the alternative splicing program of apoptotic genes such as caspase 9 (Leva et al, 2012). Notably, both the level of SRSF1 phosphorylation and splicing programs can revert to those observed in normal cells by inhibiting ATM activity, indicating that SRSF1 phosphorylation could be part of a regulatory circuit through which cells cope with DNA damage.…”
Section: Rbps May Affect the Splicing Profiles And Levels Of Mrnas Fomentioning
confidence: 99%
“…It was recently shown that genotoxic stress can induce the phosphorylation and the relocalization of these kinases to the nucleus where they in turn hyperphosphorylate SR proteins leading to changes in pre-mRNA splicing [22, 23]. Moreover, chronic replication-dependent DNA damage was shown to induce the hyperphosphorylation of ASF/SF2 (SRSF1) [24]. …”
Section: How Ddr Can Affect Alternative Pre-mrna Splicing (As)mentioning
confidence: 99%
“…During an undisturbed replication process, when the elongating DNA ends synthesized from neighbouring replicons abut, DNA ligase seals the gaps of DNA fragments and the nascent DNA becomes continuous [40]. This process is also referred to as DNA maturation of replicative intermediates for both the nascent leading strand DNA and Okazaki fragments [41], [42] (Figure 1B). Before the DNA maturation is completed the nascent DNA fragments can be unwound under alkaline conditions, indicating incomplete replication and the presence of single-stranded gaps in the newly replicated DNA (Figure 1C, left panel).…”
Section: Resultsmentioning
confidence: 99%